Defining and Activating the Role of Department Chair as Instructional Leader. Issue 2 (March 2013) - Kelley, Carolyn; Salisbury, Jason
With strong connection to schoolwide policy and vision and to the realities of the daily life of teachers and students, the department chair is uniquely positioned to play an important role in advancing instructional effectiveness (Printy, 2008; Weller, 2001). This article provides an in-depth look at the efforts of three urban comprehensive high schools to revision the role of department chair as instructional leader. The case studies identify building a shared vision, trust, role clarity, professional development, modeling, and application as critical elements of leadership development. The article defines the role of department chair as instructional leader and examines the effects of efforts to strengthen this role. Findings suggest that department chairs found their new role to be motivating and enriching, but significant training and reshaping of school norms were needed to provide the skills and legitimacy for them to lead instructional improvement in their departments.